PENGARUH KEPEMILIKAN INSTITUSIONAL, MEDIA EXPOSURE, DAN UKURAN DEWAN KOMISARIS TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Nyimas Debby Puspitadewi, (2021)
The study was conducted to examine the effect of institutional ownership, media exposure, and the size of the board of commissioners on corporate social responsibility disclosure. Corporate social responsibility disclosures are calculated based on GRI G4 and GRI Standards. The sample used is as many as 28 companies. In testing the research hypothesis using Multiple Linear Regression Analysis with the SPSS 25 program. The results of the test obtained for institutional ownership and media exposure variables have no significant effect, while for the variable size of the board of commissioners it has a significant negative effect on corporate social responsibility disclosure.